2021
DOI: 10.1038/s41598-021-02231-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota depletion from early adolescence alters anxiety and depression-related behaviours in male mice with Alzheimer-like disease

Abstract: The gut-microbiota–brain axis plays an important role in stress-related disorders, and dysfunction of this complex bidirectional system is associated with Alzheimer’s disease. This study aimed to assess the idea that whether gut microbiota depletion from early adolescence can alter anxiety- and depression-related behaviours in adult mice with or without Alzheimer-like disease. Male C57BL/6 mice were treated with an antibiotic cocktail from weaning to adulthood. Adult mice received an intracerebroventricular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…S6A), excluding the potential neurotoxicity produced by chronic intake of metronidazole. Most importantly, the antibiotic recipe with the mixture of ampicillin, vancomycin, neomycin, and metronidazole has been well accepted in the microbiota-gutbrain field for the neural and behavioral testing in rodent (Chu et al, 2019;Desbonnet et al, 2015;Gacias et al, 2016;Lupori et al, 2022;Mosaferi et al, 2021;Mukherji et al, 2013;Soto et al, 2018;Vicentini et al, 2021;Wu et al, 2020;Wu et al, 2021). Therefore, the impact of ABX on the mouse anxiety-like behavior is unlikely caused by the penetration of metronidazole.…”
Section: Discussionmentioning
confidence: 99%
“…S6A), excluding the potential neurotoxicity produced by chronic intake of metronidazole. Most importantly, the antibiotic recipe with the mixture of ampicillin, vancomycin, neomycin, and metronidazole has been well accepted in the microbiota-gutbrain field for the neural and behavioral testing in rodent (Chu et al, 2019;Desbonnet et al, 2015;Gacias et al, 2016;Lupori et al, 2022;Mosaferi et al, 2021;Mukherji et al, 2013;Soto et al, 2018;Vicentini et al, 2021;Wu et al, 2020;Wu et al, 2021). Therefore, the impact of ABX on the mouse anxiety-like behavior is unlikely caused by the penetration of metronidazole.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in this work that the TAS scores of the two groups of patients had extremely significant differences ( P < 0.01). Relevant studies have shown that adaptive emotion regulation is significantly negatively correlated with depression level in patients with depression, but not with anxiety level ( 32 ). This may indicate that patients with depression who tend to use adaptive emotion regulation strategies have relatively low levels of depression, and the individual’s adaptive emotion regulation is a protective factor.…”
Section: Discussionmentioning
confidence: 99%
“…Further support to this notion is the fact that antibiotics, such as streptozotocin, have been used to induce sporadic AD forms in animal models, thereby affecting learning and memory performance ( Cattaneo et al, 2017 ). Antibiotic treatment from early adolescence significantly decreased hippocampal BDNF and enhanced learning and memory impairments in a mouse model of multiple sclerosis ( Zeraati et al, 2019 ), and prevented the development of anxiety- and depression-related behaviors, oxidative stress and hypothalamic-pituitary-adrenal axis dysregulation in AD mice ( Mosaferi et al, 2021 ). The evidence suggests that the use of antibiotic cocktails in adolescent mice can lead to permanent changes in intestinal microflora and an increase in pro-inflammatory cytokines ( Desbonnet et al, 2014 , 2015 ; Cattaneo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%